Permeability Theory in a Social Environment: Comment on Stamps (2013). Issue 1 (August 2014) - Liu, Yang; Zheng, Rui; Sun, Yan
Stamps (2013) reported that the visual permeability of a boundary strongly influenced perceived enclosure, while boundary depth had almost no effect. Specifically, Stamps found that perceived enclosure demonstrates a highly negative correlation with distal permeability, a moderately negative correlation with proximate permeability, and a very low positive correlation with distal distance. The present comment suggests that environmental properties may affect physical perception, mental processes, and human behavior – not only in a physical but also in a social environment.